Validasi Metode Identifikasi Fenilbutazon dan Deksametason dalam Jamu Pegal Linu secara Kromatografi Lapis Tipis-Densitometri - Imelda Rindiantyas; Diana Diana; Henry Kurnia Setiawan (Prosiding Seminar Nasional Ilmu Kesehatan dan Keperawatan, 2024)
Traditional herbal medicine, known as 'Jamu,' is prohibited from containing pharmaceutical chemical substances (BKO) by the Indonesian Food and Drug Monitoring Agency (BPOM). In October 2022, BPOM released a public warning after discovering the presence of phenylbutazone and dexamethasone in a muscle pain relief jamu product. The purpose of this research is to establish a valid method for identifying phenylbutazone and dexamethasone in jamu pegal linu. In this study, the method was applied to 10 brands of muscle pain relief jamu samples. The samples were extracted with methanol and then spotted in a quantity of 5 μl on a silica gel 60 F254 plate, eluted with a selected mobile phase, namely ethyl acetate: methanol: ammonia (8.5:1:0.5, v/v/v). Spots were observed with a densitometry at λ240 nm. Phenylbutazone appeared at Rf 0.33, and dexamethasone at Rf 0.77, with a resolution value (Rs) of 5,8. The detection limits for phenylbutazone were 8,5307 μg/ml (0,1706 mg/600 mg capsule) and for dexamethasone, 8,7611 μg/ml (0,1752/600 mg capsule). The results revealed that two samples tested positive for both phenylbutazone and dexamethasone, while six samples tested positive for dexamethasone.